Seismic microzonation mapping of Greater Vancouver based on various site classification metrics - Adhikari, Sujan Raj; Molnar, Sheri; Wang, Jinfei (Frontiers in Earth Science, 2023)
The goal of the multi-year seismic microzonation mapping project for Greater Vancouver, British Columbia, Canada is to produce seismic hazard maps inclusive of local site effects, in particular seismic hazard specific to one-dimensional site response and three-dimensional Georgia sedimentary basin amplification, as well as liquefaction and landslide hazard potential. We explore the variability in key seismic site characterization measures most often used for seismic microzonation mapping to evaluate the impact to mapping and communication of seismic microzonation of Greater Vancouver. This paper focuses on comparison of seismic microzonation maps of Greater Vancouver based on up to three seismic site term parameters and their associated classification schemes: (1) the time-averaged shear-wave velocity (Vs) of the upper 30 meters (Vs30) and associated Canadian national building code site class; (2) Vs30-based site classification proposed for the updated Eurocode 8; (3) site period (T0) determined from microtremor site amplification spectra; and (4) a hybrid site classification based on T0 and the average Vs and thickness of soil. Over 890810 Vs30 and 2,200 T0 values are determined to evaluate sub-regional differences in these important seismic site parameters in Greater Vancouver. We find that seismic microzonation of Greater Vancouver depends on the chosen seismic site parameter (Vs30, T0, or a combination of parameters) and that classification scheme's with greater divisions in classes are beneficial to communicating the great variability in seismic site conditions in Greater Vancouver. We recommend that either one hybrid classification map or two classification maps of Vs30 and T0 together are required for effective communication of seismic microzonation of Greater Vancouver.